Estudo de novas alternativas biológicas na eliminação de microrganismos envolvidos nas infecções endodônticas - Lourenço, Lucas Faria Morini [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Endodontic infections occur because of the microorganisms invasion of the root canal system and can reach the periradicular tissues. The first step in endodontic therapy consisted on the elimination of microorganisms and prevention of reinfection of root canals. Herbal substances have been incorporated in various dental products, due to its anti-inflammatory, antibacterial and antifungal activities, besides no promote antibiotic resistance and be biocompatible at therapeutic concentrations, creating new biological perspectives for dental treatment. The objective of this study was to evaluate the antimicrobial action of silymarin on planktonic culture and on biofilms of Enterococcus faecalis (ATCC 51299). Planctonic assays were performed to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of silymarin. Biofilms of E. faecalis were exposed to 5X and 10X MIC silymarin (SIL) and the control chlorhexidine digluconate (CHX). After exposure for 24h, the cultures were plated on Mueller-Hinton agar and incubated for 24 hours to count the colony forming units (CFU) per ml. The data were statistically analyzed, considering p <0.05. The results showed that the SIL at 1.25mg/mL was considered CIM because reduced 51.62% of E. faecalis growth, however, only SIL at 5mg/mL was sufficient to eliminate 100% of E. faecalis and considered CBM. In biofilm tests, SIL 10x MIC was the agent who showed the best effect against biofilms of E. faecalis, reducing five logarithmic houses of E. faecalis growth. SIL 5x and 10x CHX showed similar results, reducing two logarithmic houses of E. faecalis growth. CHX 5X did not differ from controls. Concludes that silymarin has action against E. faecalis in planktonic and biofilm conditions, showing a promising biological agent for the elimination of microorganisms involved in endodontic infections

As infecções endodônticas ocorrem como resultado da invasão de microrganismos no sistema de canais radiculares podendo atingir os tecidos perirradiculares. O primeiro passo na terapia endodôntica consiste na eliminação dos microrganismos e na prevenção das reinfecções dos canais radiculares. Substâncias derivadas de plantas estão sendo incorporados em diversos produtos odontológicos, devido às suas propriedades antiinflamatórias, antibacterianas e antifúngicas, além de não promoverem resistência antibiótica e serem biocompatíveis em concentrações terapêuticas, criando novas perspectivas biológicas para o tratamento odontológico. Assim, o objetivo do presente estudo foi avaliar a ação antimicrobiana da silimarina sobre cultura planctônica e sobre biofilme de Enterococcus faecalis (ATCC 51299). Foram realizados ensaios em cultura planctônica para determinar a concentração inibitória mínima (CIM) e concentração bactericida mínima (CBM) da silimarina. Biofilmes de E. faecalis foram expostos a 5x e 10x CIM da silimarina (SIL) e controle de digluconato de clorexidina (CHX). Após exposição por 24h, as culturas foram plaqueadas em MH ágar e incubadas durante 24 horas para posterior contagem das unidades formadoras de colônias (UFC) por mL. Os dados obtidos foram estaticamente analisados, considerando p<0,05. Os resultados mostraram que a concentração de 1,25mg/mL de SIL foi considerada CIM pois reduziu 51,62% do crescimento de E. faecalis, entretanto, somente 5mg/mL de SIL foi suficiente para eliminar 100% de E. faecalis e considerada CBM. Nos ensaios de biofilme, SIL 10x CIM foi o agente que apresentou melhor efeito contra biofilme de E. faecalis, reduzindo em cinco casas logarítmicas o crescimento deste microrganismo. SIL 5x e CHX 10x apresentaram resultados...
Keywords: Biofilmes; Silimarina; Enterococcus faecalis; Biofilms